Beta2-microglobulin(B2M) in cancer immunotherapies: Biological function, resistance and remedy. (1st October 2021) - Wang, Hanbing; Liu, Baorui; Wei, Jia
Abstract: Cancer immunotherapies have made much headway during the past decades. Techniques including the immune checkpoint inhibition (ICI) and adoptive cell therapy (ACT) have harvested impressive efficacy and provided far-reaching tools for treating cancer patients. However, due to inadequate priming of the immune system, a certain subgroup of patients remains resistant to cancer immunotherapies during or after the treatment. β2-microglobulin (B2M) is an important subunit of major histocompatibility complex (MHC) class I which exerts substantive biological functions in tumorigenesis and immune control. Accumulating evidence has shown that alterations of B2M gene and B2M proteins contribute to poor reaction to cancer immunotherapies by dampening antigen presentation. Here, we discuss the basic biological functions of B2M, its distribution in a spectrum of cancers, and current understanding of its role in ICI, cancer vaccines and chimeric antigen receptor T cell (CAR-T) therapies. Furthermore, we summarize some promising therapeutic strategies to improve the efficacy inhibited by B2M defects. Highlights: B2M loss causes primary and acquired resistance to immune checkpoint inhibition therapy. B2M gene mutations occur in many cancer types, especially MSI-H cancers. B2M plays multifaceted role in cancer immune control. Several immunotherapies are promising approaches to handling B2M-realted resistance.